2016
DOI: 10.1016/j.ecss.2015.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Formation and structure of the turbidity maximum in the macrotidal Charente estuary (France): Influence of fluvial and tidal forcing

Abstract: a b s t r a c tUnderstanding estuarine sediment dynamics and particularly turbidity maximum dynamics is crucial for the management of these coastal systems. Various processes impact the formation, movement and structure of the turbidity maximum. Several studies have shown that tidal asymmetry and density gradients are responsible for the presence of this suspended sedimentary mass.The Charente estuary is a highly turbid system (with suspended sediment concentrations often in excess of 5 g/L) that remains poorl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 54 publications
4
33
0
1
Order By: Relevance
“…This trend of shorter length at high tide is consistent with the analysis of the Charente ETM by Toublanc et al [19]. It is likely explained by the salinity distribution.…”
Section: General Patterns Of Etmssupporting
confidence: 79%
See 1 more Smart Citation
“…This trend of shorter length at high tide is consistent with the analysis of the Charente ETM by Toublanc et al [19]. It is likely explained by the salinity distribution.…”
Section: General Patterns Of Etmssupporting
confidence: 79%
“…The convergence at the saltfront of landward sediment flux by the gravitational circulation and seaward sediment flux by the river flow is considered as a fundamental mechanism contributing to ETM formation [17][18][19]. In most estuaries, tidal resuspension has been recognized as a key factor in maintaining high SPM concentration [13,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Turbulent mixing also decays from the upper estuary down to the stratified saline intrusion zone, so that sediment settling (and trapping) is enhanced in the latter area (Geyer, ). Recently, Toublanc et al () concluded that, in the highly turbid Charente Estuary (with SSCs often exceeding 5 g/L), the tidal asymmetry was the main mechanism leading to the ETM formation, whereas the density gradients contributed to maintaining the ETM stability. Vertical stratification trapped sediment at the bottom and the longitudinal density gradients ensured a sharper concentration gradient at the downstream limit of the ETM, preventing a massive export of sediments.…”
Section: Introductionmentioning
confidence: 99%
“…YU et al, 2014 ;MCSWEENEY et al, 2016 ;JALON-ROJAS et al, 2016 ;TOUBLANC et al, 2016). De plus, la remise en suspension des sédiments sur les bancs à l'embouchure et les opérations de dragage le long des chenaux de navigation jouent un rôle très important (AVOINE et al, 1981 ;LE HIR et al, 2001 ;MARMIN et al, 2014).…”
Section: Introductionunclassified